Studi Potensi Subak Renon di Denpasar Selatan untuk Pengembangan Agrowisata - I GEDE ARYA SANJAYA; COKORDA GEDE ALIT SEMARAJAYA SEMARAJAYA; I NYOMAN GEDE ASTAWA ASTAWA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT The Study of Potential of Subak Renon in South Denpasar for Agrotourism Development The purpose of this study is to determine and develop the potential contained in the Village of Renon in general and Subak Renon in particular so it can develop Subak Renon as a region for agrotourism, and to know what kind of recreation that can be developed in Subak Renon. This research is descriptive qualitative. Primary data are obtained from direct observation and interviews, and secondary data are obtained from the study of literature. Based on the results of research on Subak Renon, was found that the natural condition of the site was developed, thus becoming a potential that can support the agrotourism.potential in Subak Renon includes a wide range of commodities, there are farmers activity inside, farm large enough for the development of agrotourism, the infrastructure include Bangun Bagi, irrigation, farm roads, rice paddies, jineng, bale subak, bale timbang, subak temples, original condition thus supporting the development of agrotourism in Subak Renon. Based on the potential contained on the site, includes objects, activities, and facilities, the types of recreation that can be developed, are physical recreation, social recreation, cognitive recreation, and the recreation of natural environment. Keywords : potential, subak, agrotourism.